2020
DOI: 10.1002/smll.202001053
|View full text |Cite
|
Sign up to set email alerts
|

Electrolyte‐Dependent Sodium Ion Transport Behaviors in Hard Carbon Anode

Abstract: A comprehensive study is conducted on hard carbon (HC) series samples by tuning the graphitic local microstructures systematically as an anode for SIBs in both carbonate‐ (CBE) and glyme‐based electrolytes (GBE). The results reveal more detailed charge storage characters of HCs on the LVP section. 1) The LVP capacity is closely related to the prismatic surface area to the basal plane as well as the bulk density, regardless of electrolyte systems. 2) The glyme‐sodium ion complex can facilitate sodium ion delive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 53 publications
0
26
0
Order By: Relevance
“…The full cell of HCM-1300-ZBE delivered a high energy density of 294.6 Wh kg -1 , and a high power density of 6.73 kW kg -1 (based on total mass of both electrodes, Figure 2h), surpassing the previously reported high-energy and high-power full cell (Table S14, Supporting Information). [2,17,33,[59][60][61][62][63][64][65]…”
Section: Electrochemical Characterizationmentioning
confidence: 99%
“…The full cell of HCM-1300-ZBE delivered a high energy density of 294.6 Wh kg -1 , and a high power density of 6.73 kW kg -1 (based on total mass of both electrodes, Figure 2h), surpassing the previously reported high-energy and high-power full cell (Table S14, Supporting Information). [2,17,33,[59][60][61][62][63][64][65]…”
Section: Electrochemical Characterizationmentioning
confidence: 99%
“…Recently, it was exceptional that the solvent co-intercalation behavior in an ether-based electrolyte was demonstrated in a hard carbon electrode, facilitating fast sodium storage and a high-rate performance. 110,199,200 In a previous study on lithiumpenetrated hard carbon electrode, Li et al 199 conducted ab initio molecular dynamics (AIMD) simulations to understand the effect of an ether electrolyte (TEGDME) on sodium intercalation. The structural evolution of hard carbon was simulated in the system of NaClO 4 -TEGDME electrolyte.…”
Section: Hard Carbonmentioning
confidence: 99%
“…However, the large amounts of defects and active surface in the hard carbon can induce electrolyte decomposition also. 200 The underlying mechanism of enhancing the rate and cycling capability of hard carbon in ether-based electrolytes was also investigated. 201 They found that the pillar ether solvent helped modulate the interfacial crystallographic structures of hard carbon, which functioned as a ''pseudo-SEI'' to facilitate fast sodium storage kinetics (Fig.…”
Section: Hard Carbonmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the type of electrolyte also affects the electrochemical behavior, that is, certain carbons behave differently in different solvents. [60,61] The typical voltage-capacity discharging profile of hard carbon is shown in Figure 2 and consists of at least one or two sloping regions (0.1-2.0 V, vs Na + /Na) and a plateau region (below 0.1 V, vs Na + /Na). The high capacity and high voltage of hard carbons as compared to soft carbons or graphite can be ascribed to a longer voltage plateau.…”
Section: Current Status Of Fundamental Sodium Storage Mechanismmentioning
confidence: 99%